IMPLEMENTASI PENDIDIKAN AKHLAK DI PONDOK PESANTREN MIFTAHUL HUDA MALANG - Damanhuri, Damanhuri (AS-SALAM, 2015)
Indonesian nation is undergoing a severe trial by the increasingmoral decline of the nation . Corruption , drugs , sex, fights andmany other deviant behavior that everyday adorn the local andnational media . Formal education institutions predicted aschurning generation of people has not been fully able to carryout the mandate of the national education goals in the printgeneration morality . That is where boarding Miftahul Hudaemerged as an alternative in efforts to reduce the destructiveimpact caused by the rate of change of era. The results showedthat Ponpes Miftahul Huda has good concept in coaching noblecharacter of students . Implementation of noble charactereducation in schools is done integrally through two mainpoints , namely teaching and habituation . Teaching studentsto understand the cognitive aspects as well as habituation bydirectly applying an understanding that has been gained ineveryday activities .Keywords : Moral Education , Ponpes Miftahul Huda